(untitled) (Biomedical Research and Therapy, 2023)
Introduction: Statins are frequently prescribed for patients with hyperlipidemia to prevent cardiovascular disease, however, there is an inter-individual variability in their efficacy due to many factors, including genetic polymorphism. This study aimed to determine the association between single nucleotide polymorphism (SNP) in the gene cluster SORT1-CELSR2-PSRC1 (rs646776) and lipid profiles in a subset of statin users in Malaysia. Methods: In total, 122 statin-treated patients were recruited in this cross-sectional study. Genomic DNA from whole blood samples (3 mL) was extracted and genotyped using amplification-refractory mutation system-polymerase chain reaction (ARMS-PCR) for the rs646776 polymorphism. The association between the SNP and statin-related lipid profile changes was evaluated using a dominant genetic model (AA vs. GA + GG genotypes). Results: The minor allele frequency of the rs646776 was 0.08 and the allele frequency of each genotype was in the Hardy–Weinberg equilibrium (P = 0.6149). Variant allele carriers of rs646776 showed higher (P < 0.05) high-density lipoprotein cholesterol (HDL-C) levels after statin treatment in females but not in males. Conversely, AA genotypes were linked to a significant decrease in total cholesterol and low-density lipoprotein cholesterol (P < 0.01). Conclusion: Our study provides the first frequency data for PSRC1/CELSR2/SORT1 rs646776 in the Southeast Asian region and further confirms the SNP association with improved HDL-C levels, especially in females using statins. The findings warrant further replication studies to validate the SNP association among different ethnicities in Asia.